Simulation Methods and Sensitivity Testing on NPK Fertilizer Production in Warehouse Stackage Management (Case Study at Pt Pupuk Kujang) - Aqmar Sulton Aulia; Muhamad Iqbal; Alfin Agung Ramadhan; Fawwaz Jannuranti; Yuanita Suliandri (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
PT Pupuk Kujang, as one of Indonesia’s national fertilizer producers, faces inventory accumulation problems of NPK fertilizer in warehouses due to an imbalance between production capacity, storage capacity, and seasonal market demand. Excessive stockpiling exceeding standard storage limits, reaching up to 40 stacks, leads to increased operational costs and product damage risks of up to 20–30 percent, thereby reducing operational efficiency. This study aims to analyze the management of NPK fertilizer accumulation in warehouses and to determine optimal production scheduling and storage capacity policies through simulation methods and sensitivity analysis. The research applies a system dynamics approach using Causal Loop Diagram (CLD) and Stock Flow Diagram (SFD) models developed with AnyLogic software, complemented by supply chain simulation using SCM Globe. The study utilizes secondary data on NPK fertilizer production and distribution at PT Pupuk Kujang from 2015 to 2017. Simulation results indicate that inventory accumulation is primarily caused by inflexible production schedules that do not adequately adjust to seasonal demand fluctuations influenced by planting cycles and weather conditions. Sensitivity analysis results show that the scenario with a warehouse capacity of 25 stacks represents the most optimal condition, as it significantly reduces inventory buildup without disrupting distribution activities. This study recommends implementing more adaptive production scheduling and optimizing warehouse capacity and distribution systems to enhance operational efficiency and minimize the risk of product damage.